Novel binding sites on GABA (A) receptors for the alternative effects of zolpidem: in vivo and in silico studies - Mohamad, Fatin Hilyani (2023)
Patients with brain injuries commonly suffered significant motor and cognitive decline which interfere with their recovery process. To improve the quality of life in these patients, pharmacological intervention targeting the motor and cognitive functions are usually administered. There have been reports on the awakening effects of the sleeping pill, zolpidem when administered to patients with different types of brain injury. Since the sedative and hypnotic effect of the drug is elicited from the α(1/2/3/5)-γ interface of GABA (A) receptor, it is possible that this effect is contributed from different binding sites which have not been explored before. Hence, this thesis aimed to investigate the molecular and pharmacological reason behind this paradoxical effect through zolpidem administration in animal behavioural studies (in vivo) supported with analysis on protein-ligand complex through computational methods (in silico). These rats with induced ischaemic injury and impaired cognitive functions were given different doses of zolpidem (control, saline, 1.0, 2.0 and 4.0 mg/kg) and underwent open-field test and Morris water maze tests. Zolpidem administration on these animals showed improvement from the groups receiving 1.0 mg/kg zolpidem in comparison to the non-treated and those receiving higher doses of zolpidem. Further, immunohistochemistry study showed significant effects on the expression of hippocampal α1 and ε subunits of GABA (A) receptors. The observations suggested; both subunits have complementary action during ischaemic injury and both subunits have modulatory action towards 1.0 mg/kg of zolpidem. To prove this, binary α1β3α1 and GABA (A) ε-containing receptors were created using homology modelling technique and molecular docking of zolpidem were performed at several targeted interfaces of these receptors, followed by molecular dynamics simulation. Comparison of energy binding, protein-ligand interaction and structural stability to the control α1+-γ2- interface of α1β3γ2 GABA (A) receptor, showed potential binding action of zolpidem towards α1+-α1- interface from binary α1β3α1 and α1+-ε- interface of α1β3εε GABA (A) receptors. Even though the mechanism on how exactly these interfaces contribute to the awakening action of zolpidem is not revealed, these data are still able to demonstrate the binding affinity of zolpidem towards the novel binding sites of α1+-α1- and α1+-ε- interfaces. As a result, proving the existence of other binding sites of zolpidem within GABA (A) receptors possibly created due to subunit rearrangement in post-brain injuries, which could have caused the awakening action of zolpidem.